On the refinement of the remainder term in the multidimensional central limit theorems - Bikelis, A. (Lithuanian Mathematical Journal, 1964)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. Бикялис. Об уточнении остаточного члена в многомерной центральной предельной теореме A. Bikelis. Apie liekamojo nario pagerinimą daugiamatėje centrinėje ribinėje teoremoje